2022
DOI: 10.1109/jssc.2022.3168588
|View full text |Cite
|
Sign up to set email alerts
|

A 7.3-μ W 13-ENOB 98-dB SFDR Noise-Shaping SAR ADC With Duty-Cycled Amplifier and Mismatch Error Shaping

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
(72 reference statements)
0
11
0
3
Order By: Relevance
“…In some cases, the loop-filter is fully passive (i.e. : made with switches and capacitors) [26], while in other cases an active filter is made, typically based on a simplified yet highly-efficient amplifier [27]. While the first category benefits from lowest power consumption, the additional kT /C noise terms either impact the SNR, or otherwise relatively large capacitors might be required.…”
Section: B Sar Adcs With Noise Shapingmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the loop-filter is fully passive (i.e. : made with switches and capacitors) [26], while in other cases an active filter is made, typically based on a simplified yet highly-efficient amplifier [27]. While the first category benefits from lowest power consumption, the additional kT /C noise terms either impact the SNR, or otherwise relatively large capacitors might be required.…”
Section: B Sar Adcs With Noise Shapingmentioning
confidence: 99%
“…The active filters enable a higher SNR at the cost of increased power consumption. A review of active filters can be found in [27]. Also, since the SAR quantizer can have a reasonably high resolution, both the filter and the oversampling ratio can For illustration, a recent example of a NS-SAR ADC is shown in Fig.…”
Section: B Sar Adcs With Noise Shapingmentioning
confidence: 99%
See 1 more Smart Citation
“…Transconductance amplifers transform voltage signals into current signals in analog and mixed-signal electronics. Te entire efcacy of diferent applications such as signal processing, communication systems, and sensor interfaces is determined by their performance [6,7]. Te ability to tune amplifer characteristics is crucial in adapting these circuits to varied settings without sacrifcing efciency [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the area and mismatch of the digital-to-analog converter (DAC) makes it difficult to achieve high-resolution characteristics. SAR ADCs using noise shaping (NS) have been proposed as an alternative to the resolution enhancement limitations of SAR ADCs [9,10], but there are still structural difficulties in implementing resolutions above 14-16 bits. Delta-sigma ADCs typically use analog integrators with op amps, which have the disadvantage of relatively increased power consumption and area, but they have been widely used in high-performance sensor interfaces because they have a suitable structure to achieve high resolution [1][2][3][4][5][6]11,12].…”
Section: Introductionmentioning
confidence: 99%